2015
DOI: 10.1002/jwmg.905
|View full text |Cite
|
Sign up to set email alerts
|

Captive rearing sage-grouse for augmentation of surrogate wild broods: Evidence for success

Abstract: Both species of North American sage‐grouse (Centrocercus spp.) have experienced declines in distribution and abundance. Translocation of adult birds from a stable population to a small or declining population has been a management tool used by wildlife managers to support population persistence in these areas. Captive rearing chicks and releasing them into wild surrogate broods is an untested alternative to augment declining populations of sage‐grouse. We developed techniques to successfully rear sage‐grouse c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 67 publications
3
17
0
Order By: Relevance
“…We found comparable patterns of survival between wild and domestically hatched juveniles into the fall and through brood break‐up. Our findings further support Thompson et al () who suggested that captive‐rearing techniques could be used to augment demographically challenged sage‐grouse populations (Apa and Wiechman , ), but the technique could be less successful in extreme environments (e.g., Cold Springs Mountain).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We found comparable patterns of survival between wild and domestically hatched juveniles into the fall and through brood break‐up. Our findings further support Thompson et al () who suggested that captive‐rearing techniques could be used to augment demographically challenged sage‐grouse populations (Apa and Wiechman , ), but the technique could be less successful in extreme environments (e.g., Cold Springs Mountain).…”
Section: Discussionsupporting
confidence: 89%
“…Wildlife managers need a better understanding of age‐specific demographic rates and how they are related to local and regional landscapes in relation to movement patterns, population levels, and habitat use to manage sage‐grouse. We further support recommendations by Thompson et al () that captive‐reared sage‐grouse can recruit to the population and that captive rearing could be used as a potential management strategy for demographically challenged sage‐grouse populations (Apa and Wiechman , ). Although demography research is expensive and logistically challenging, long‐term studies are needed to account for spatial and temporal variability.…”
Section: Management Implicationssupporting
confidence: 88%
See 2 more Smart Citations
“…However, there was little evidence for overdispersion in our juvenile survival analysis (ĉ ¼ 1.103). The lack of overdispersion in our juvenile data may in part have been due to brood mixing, which occurs at a relatively high rate within sage-grouse , Dahlgren et al 2010, Thompson et al 2015 and was observed in our study.…”
Section: Discussionmentioning
confidence: 55%